PENGARUH KEPERCAYAAN, KUALITAS PELAYANAN, HARGA DAN WORD OF MOUTH (WOM) TERHADAP KEPUTUSAN PEMBELIAN JASA WEDDING ORGANIZER KELUARGA BABA DI KOTA PALEMBANG: PENGARUH KEPERCAYAAN, KUALITAS PELAYANAN, HARGA DAN WORD OF MOUTH (WOM) TERHADAP KEPUTUSAN PEMBELIAN JASA WEDDING ORGANIZER KELUARGA BABA DI KOTA PALEMBANG - Ewaka, Langi; Ayu, Charisma (Sekolah Tinggi Ilmu Ekonomi (STIE) Aprin, 2023)
Abstract This study aims to analyze the influence of trust, service quality, price and word of mouth on the decision to purchase wedding services for the Baba Family organizer in Palembang City. This study used a descriptive quantitative method with a sample of 182 respondents. Methods of data analysis using non-probability sampling, purposive sampling, as well as multiple regression with the SPSS 26 statistical test tool. Based on the results of the study it showed that the variables of trust, quality of service, price and word of mouth (wom) had a significant and positive effect partially or simultaneously on the decision to purchase the services of a baba family wedding organizer in the city of Palembang.